Probiotic topical application for acne management (Research, Society and Development, 2023)
In recent years, an increasing number of studies have been conducted on probiotics and their benefits in various skin conditions, including acne, which is characterized by increased accumulation of sebum and keratin in pilosebaceous follicles that promotes the proliferation of Cutibacterium acnes and causes dysbiosis in the microbiome. Acne primarily affects adolescents and can be triggered by hormonal, genetic, and nutritional factors. Currently prescribed treatment for acne is effective, but in many cases has adverse effects that harm patients. In contrast, probiotics have shown promise as a therapeutic alternative, not only when administered orally, but also when applied topically with local effects and no undesirable side effects. The main mechanism of action of probiotics is their ability to promote skin homeostasis. Therefore, interest in the use of topical probiotics for the treatment of acne has increased, with the aim of analyzing the most commonly used probiotic strains and their use and effects on the skin in reducing acne. Through the integrative review method in the bibliographic search of Science Direct, PubMed, Scielo, ScienceDirect and Google Scholar databases, using the descriptors "Acne"," "Probiotics" and "Lactobacillus" and using the Boolean operator "AND"," clinical studies were prioritized between 2010 and 2022. All the studies reviewed showed unanimity regarding the effect of probiotics in reducing acne, with satisfactory results in over 90% of the cases studied.